Quality of Service at the Office Environment of National Political Unity and Community Protection of Mentawai Islands Regency - Posmaria Siallagan; Isfarudi Isfarudi; Hendri Koswara (Science and Environmental Journal for Postgraduate, 2023)
This study aims to 1) explain the quality of skill certificate services at the Office of National Political Unity and Community Protection of Mentawai Islands Regency; 2) Analyze the effectiveness of the implementation of its skill certificate services; and 3) Develop strategies for the Office of National Political Unity and Community Protection of Mentawai Islands Regency in improving services to the community to be more efficient and effective. This research uses a qualitative approach. Data collection was carried out to parties who manage skill certificates using questionnaires. The results showed that in general, the effectiveness of skill certificate services in Mentawai Islands Regency has not reached a good predicate. That is, even though the service in question is still limited to one employee, it can still be overcome. The level of unsatisfactory service satisfaction is caused by several problems, including 1) The element of accumulative requirements for skill certificate management services is only considered limited as long as it meets the standards only; 2) Elements of procedures that are considered to have not met the wishes of the community; 3) The level of public satisfaction with the length of service is perceived to have not met the wishes of the applicant community; 4) The level of public satisfaction with skill certificate services for elements of complaint handling that are considered to have not met the wishes of the applicant community.